Interrelationship Between Green Supply Chain Management and Green Innovation in Sustainability: A Systematic Literature Review - Muhammad Surya Dwi Kurniawan; Sri Hartini (Jurnal Ilmu Lingkungan, 2025)
The trend of GSCM has gained popularity in many developed countries with the intention of decreasing to mitigate its adverse effects on environmental stability. GSCM is linked to several other variables such as Green Innovation in Sustainability. There have been numerous theoretical and empirical studies on the topic. However, in developing countries, there is still limited research and knowledge about GSCM, GI, and their influence on Sustainable Performance. Therefore, this research aims to enrich the current literature on research and practices. It helps in systematically researching published articles, using systematic literature review to analyze large datasets related to the topic. Additionally, the results of this study will aid upcoming researchers in gaining insights into current research trends and themes in the field of GSCM, GI, and Sustainability.